If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(d-2)=5(d-3)+2d+1)
We move all terms to the left:
7(d-2)-(5(d-3)+2d+1))=0
We multiply parentheses
7d-(5(d-3)+2d+1))-14=0
| b÷13-3b÷13=8/13 | | 1000=1.5t-300 | | 3-7k=3-3k | | 6=2n−8;7 | | -28-n=4(n+3) | | 8+x/3=-10 | | -8j+3=2j+11 | | (x-3)=36 | | 6=(x+11) | | -14=x-11 | | 9m=26-4m | | 5(m+9)=2m | | 4p-9.2p=-2.6+5.3= | | (2x+1)/3=1/4 | | (x-3)^2=36 | | 3/4x-6=21 | | -6x=2(x+2)=36 | | 5w-3=8w+10 | | -9b-13=-103 | | 10x=7x+33 | | .-3(4r-8)=-36 | | x^=35+ | | 1/6x+1=1/4x-1 | | x^2+3x-5/2=0 | | X-7=-5x+23 | | .8(x-40)=x(.6) | | 3(x+7)-x+9=30 | | 4-x/2=3 | | 35x-2(x+30)=48+3x | | 5(+9)=2m | | 8w+10=5w-3 | | 7(x-2)+3(x+4)-6(x-2)=0 |